Real-world effectiveness and safety of Baloxavir Marboxil or Oseltamivir in outpatients with uncomplicated influenza A: an ambispective, observational, multi-center study - Cai, Jianpeng; Wang, Hongyu; Ye, Xiaoting; Lu, Shengjia; Tan, Zhili; Li, Zhonghua; Lin, Dan; Qian, Jiancheng; Lu, Xiaoxian; Wan, Jiaolong; Wang, Jie; Ai, Jingwen; et al. (Frontiers in Microbiology, 2024)
Baloxavir Marboxil is a per oral small-molecule antiviral for the treatment of influenza. While the efficacy and safety of Baloxavir Marboxil have been thoroughly characterized across an extensive clinical trial, studies on the effectiveness of Baloxavir Marboxil in a real-world setting are still scarce. We conducted an ambispective, observational, multi-center study that enrolled uncomplicated influenza outpatients treated with Baloxavir Marboxil or Oseltamivir in East China. The primary endpoint was time from treatment to alleviation of all influenza symptoms (TTAIS). The secondary endpoints included time from treatment to alleviation of fever (TTAF) and household transmission during the duration of influenza. A total of 509 patients were enrolled. The median TTAIS in the Baloxavir Marboxil group and the Oseltamivir group was 28.0 hours (IQR, 20.0 to 50.0) and 48.0 hours (IQR, 30.0 to 67.0), respectively. The median TTAF in the Baloxavir Marboxil group and the Oseltamivir group was 18 hours (IQR, 10.0-24.0) and 30.0 hours (IQR, 19.0-48.0). In the COX multivariable analysis, Baloxavir Marboxil reduced the duration of influenza symptoms (HR=1.36 [95%CI:1.12-1.64], P=0.002) and the duration of fever (HR=1.93 [95%CI:1.48-2.52], P<0.001) compared to Oseltamivir. When antiviral drugs were given within 12-48 hours after symptom onset, the Baloxavir Marboxil group had a significantly shorter TTAIS compared to the Oseltamivir group. There was no significant difference in the rate of adverse events between the two group (P=0.555). Baloxavir Marboxil was superior to Oseltamivir in alleviating influenza symptoms in outpatients with uncomplicated influenza. Our findings suggested that compared to Oseltamivir, Baloxavir Marboxil might be more appropriate for patients with influenza 12-48 hours after symptom onset.